Archaische Siedlungsbefunde in Ephesos, Textband - von Miller, Alexandra Ch. J. (Verlag der Österreichischen Akademie der Wissenschaften, 2021)
The study deals in a holistic manner with the archaic settlement residuals (stratigraphy, architectural remains, pottery and small finds) from excavations underneath the Tetragonos-Agora at Ephesos. The findings from other two find spots are included in order to better discuss typo-chronological and functional questions.